Ordinary Representations as the Basis for Shaping Future Educators’ Scientific-pedagogic Knowledge about Personal Identity - Shakurova, Marina Viktorovna (International Review of Management and Marketing, 2016)
The author substantiates the necessity of taking into consideration teacher training university students’ ordinary representations of identity as a component of intensive way of professional-pedagogic training in shaping different kinds of social and cultural identity in schoolchildren. Use of ordinary representations ensures providing continuity, strength, personal significance of acquired scientific and professional knowledge. The research methodology involves socio-cultural approach, intersubjective approach towards interpretation of identity, as well as approach focused on personal activity in the analysis of pedagogic practices. The author determines the peculiarities of “framework theories” spontaneously formed in world outlook of students of the teacher training university in the process of their professional training, using materials of empirical research (questioning techniques, as well as association and cinquain techniques). The differences between senior students’ ordinary-professional representations of identity and younger students’ ordinary representations of it are revealed. Typical (invariant) and singular (variational) characteristics, used by students for describing identity on conceptual, associational, and systemic-descriptional level, are defined. Unidimensionality of perceiving identity as sameness, similarity, belonging; the use of this concept for characterizing the human being, her self-determination; the presence of a certain share of statements with negative connotations in which identity is regarded as antipode of singularity, originality, unique personality; abstractedness, isolation from professional practice are all referred as the typical characteristics. The conclusion is drawn that unsystematic approach towards giving professional knowledge to future educators in the field of identity studies is invalid. Keywords: teacher training; identity; social and cultural identity of personality JEL Classifications: I200, I210, Z130